Monocyte/Lymphocyte Ratio and Cardiovascular Disease Mortality in Peritoneal Dialysis Patients - Yueqiang Wen; Xiaojiang Zhan; Niansong Wang; FenFen Peng; Xiaoran Feng; Xianfeng Wu (Mediators of Inflammation)
Objectives. The monocyte-to-lymphocyte ratio (MLR), as a new marker of the systemic inflammatory response, is associated with cardiovascular disease (CVD) mortality in the general population and hemodialysis patients. However, the association between the MLR and CVD mortality in peritoneal dialysis (PD) has received little attention. Methods. In this multicenter retrospective cohort study, 1753 incident PD patients from November 1, 2005, to June 30, 2017, with a baseline MLR were enrolled. The primary endpoint was CVD mortality. The association of MLR with CVD mortality was assessed using a multivariable-adjusted Cox model and the Fine and Gray competing risk model. Results. Of 1753 patients, the mean age was 51.1±14.9 years, 56.9% of patients were male, and the Charlson comorbidity index was 4.29±1.75. During the follow-up period of 31.2±18.4 months, 368 patients died, of which 200 (54.3%) deaths were caused by CVD events. CVD mortality rates for the lowest, middle, and highest MLR tertiles were 70.6, 78.4, and 88.9 per 1000 patient-years, respectively (P<0.001). Kaplan-Meier analysis revealed that survival rates were significantly different among the three MLR groups (log rank=22.41, P<0.001). After adjusting for confounding factors, the highest MLR tertile was significantly associated with a hazard ratio (HR) for CVD mortality of 1.45 (95% confidence interval, 1.13-2.51, P=0.016). The Fine and Gray method analysis showed that using all-cause mortality as competing risk, the highest MLR tertile remained an independent predictor of CVD mortality (HR=1.39, 95% CI 1.10-2.47, P=0.021). Conclusions. Higher MLR levels at the commencement of PD may be independently associated with increased CVD mortality in PD patients.